TEACHING WRITING DESCRIPTIVE TEXT THROUGH COLLABORATIVE LEARNING - Madehang, Madehang (Institut Agama Islam Negeri Palopo, 2015)
Collaborative learning is an umbrella term for a variety of educational approaches involving joint intellectual effort by students, or students and teachers together. Usually, students are working in groups of two or more, mutually searching for understanding, solutions, or meanings, or creating a product. Collaborative learning activities vary widely, but most center on studentsâ exploration or application of the course material, not simply the teacherâs presentation or explication of it. Collaborative learning represents a significant shift away from the typical teacher centered or lecture-centered milieu in college classrooms. The writing descriptive text can be easy by using collaborative learning since the share and peer feedback during the learning writing process.